Roots of musicality : music therapy and personal development - Perret, Daniel Gilbert, 1950- (J. Kingsley Publishers, 2005)
''This is a book about music and the human spirit. It ... explain[s] how the spirit of a child may be enlivened by music. Daniel Perret ... plays in dialogue with young minds and bodies to liberate them from restraint and isolation. ... There is always a chance that music will spark the fire of life and creativity, setting a spirit free and bringing happiness. ... In skilled and sympathetic hands, it can educate and heal.''. - From the Foreword by Colwyn Trevarthen. Roots of Musicality offers an accessible and original theoretical approach to a holistic music therapy based on the notion of musicalit.